Da construção dos fundamentos do Direito em John Rawls - Roschildt, João Leonardo Marques (2010)
The focus of the present work is the construction of a concept of Right that is compatible with the notion of justice formulated by John Rawls. The verification of the formal and material structures of justice as fairness will finish determining the type of Right that fits to the Rawlsian thought, which is the interpretative doctrine. Thus it is appropriate to emphasize that the theory of the Right in Rawls is opposed to legal positivism, showing itself independent as a liberal political conception of justice so require